Rapid coastal spread of First Americans: Novel insights from South America's Southern Cone mitochondrial genomes - Bodner, Martin; Perego, Ugo A.; Huber, Gabriela; Fendt, Liane; Röck, Alexander W.; Zimmermann, Bettina; Olivieri, Anna; Gómez-Carballa, Alberto; Lancioni, Hovirag; Angerhofer, Norman; Bobillo, Maria Cecilia; Corach, Daniel; et al. (Genome Research, 2012)
It is now widely agreed that the Native American founders originated from a Beringian source population ∼15–18 thousand years ago (kya) and rapidly populated all of the New World, probably mainly following the Pacific coastal route. However, details about the migration into the Americas and the routes pursued on the continent still remain unresolved, despite numerous genetic, archaeological, and linguistic investigations. To examine the pioneering peopling phase of the South American continent, we screened literature and mtDNA databases and identified two novel mitochondrial DNA (mtDNA) clades, here named D1g and D1j, within the pan-American haplogroup D1. They both show overall rare occurrences but local high frequencies, and are essentially restricted to populations from the Southern Cone of South America (Chile and Argentina). We selected and completely sequenced 43 D1g and D1j mtDNA genomes applying highest quality standards. Molecular and phylogeographic analyses revealed extensive variation within each of the two clades and possibly distinct dispersal patterns. Their age estimates agree with the dating of the earliest archaeological sites in South America and indicate that the Paleo-Indian spread along the entire longitude of the American double continent might have taken even <2000 yr. This study confirms that major sampling and sequencing efforts are mandatory for uncovering all of the most basal variation in the Native American mtDNA haplogroups and for clarification of Paleo-Indian migrations, by targeting, if possible, both the general mixed population of national states and autochthonous Native American groups, especially in South America.
10.1101/gr.131722.111